2009
DOI: 10.1111/j.1365-2044.2008.05734.x
|View full text |Cite
|
Sign up to set email alerts
|

Open vs specific questioning during anaesthetic follow‐up after Caesarean section

Abstract: SummaryWords with negative emotional content such as pain or itch may enhance perception of these symptoms. We assessed open and direct questioning for symptoms in 100 women following Caesarean section. Of the 65 women reporting pain, 25 (39%) did so only when questioned specifically. Similarly, three women with bothersome pain (5%), and two requesting analgesia (3%), failed to disclose pain until questioned specifically. None of the 46 women with pain scores < 6 on a verbal numerical rating scale requested ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…Recently, studies have shown that women after cesarean section are more likely to report pain when asked “Do you have any pain?” compared with when women are asked “Are you comfortable?” for assessment of pain. [89] In our study also, we found that the incidence of reported pain was significantly more in Group P compared to Group C. This might be due to the reason that use of negative words gives a negative suggestion of sensations as pain that might have not been experienced otherwise.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Recently, studies have shown that women after cesarean section are more likely to report pain when asked “Do you have any pain?” compared with when women are asked “Are you comfortable?” for assessment of pain. [89] In our study also, we found that the incidence of reported pain was significantly more in Group P compared to Group C. This might be due to the reason that use of negative words gives a negative suggestion of sensations as pain that might have not been experienced otherwise.…”
Section: Discussionsupporting
confidence: 55%
“…[7] Recently, studies have documented that the use of word “comfort” rather than the word “pain” may affect patient's experience of their recovery. [8910] However, further investigations are needed to validate the results of these studies in our patient population.…”
Section: Introductionmentioning
confidence: 92%
“…This concept has been validated in a variety of other studies in obstetric anesthesia and other similar settings. [15][16][17][18][19] We can indeed influence our patient's experiences by small subtle behavioral changes! Third, anesthesiologists can enhance women's experience of care by advocating for changes in hospital policies and protocols that afford women greater control in birth.…”
mentioning
confidence: 99%
“…is important to identify all patients who may benefit from treatment. 12 A survey of 100 women following cesarean delivery found that open questions (''How are you feeling?'' and ''Are you comfortable at the moment?'')…”
Section: Communicationmentioning
confidence: 99%